Limitations on the President’s Term of Office from Maslahah Mursalah’s Perspective (Ijtihad as Determination of Islamic Law) - Hanifah Kusumastuti; Imron Rosyadi; Rizka (Universitas Muhammadiyah Surakarta, 2023)
The dynamics of the presidential term in Indonesia have lasted since the Old Order, New Order, to the Reform Era. The regulations regarding the term of service of the head of state in this country have been changed several times and often invite pros and cons, as if they are never satisfied with being used as a topic of discussion about politics and power. The constitution that regulates this issue has even been amended. The idea of amending regulations related to limiting the presidential term of office has re-emerged at any time, especially in the midst of the heated political situation ahead of the general election. To examine the presidential term, a broader perspective is needed. The transcendental paradigm regarding restrictions on the head of state in Indonesia can not only be seen from a legal perspective, but also through ethical, moral and religious values. As a country with a majority Muslim population, the position of president can be reviewed under Islamic law. Maslahah Mursalah as a method of ijtihad can be used as a tool to analyze whether restrictions on presidential office are in line with the principles of benefit and preventing harm. This research uses the library research method, by analyzing positive legal regulations, Islamic law, as well as scientific literature related to this issue. The conclusion obtained from the writing is that limiting the presidential term of office is necessary and fulfills the requirements of the maslahah mursalah. This is because limiting the term of office of the head of state is a new problem that is not explained qathi in the two main sources of Islamic law, the Qur'an and the hadith, is enforced on the basis of values of the public interest, not individuals or groups, and contains the values of benefit and prevent harm.